Comparison of Survival Outcomes between Modified Radical Mastectomy and Breast Conserving Surgery in Libyan Women with Early Breast Cancer (مجلة الرازي الطبية, 2026)
The early stage of breast cancer requires modified radical mastectomy (MRM) or breast conserving surgery (BCS). However, there are disagreements regarding the outcome of these two types of therapies in terms of patient outcomes. This study aimed to assess the overall survival and disease-free survival in Libyan women with early stages of breast cancer who underwent MRM and those treated by BCS. A total of 225 women with breast cancer (stage I and II) treated at the National Cancer Institute, Misurata, Libya, were retrospectively evaluated. 168 patients (74.7%) underwent MRM, and 57 patients (25.3%) received BCS. The associations between survival outcomes and different surgical modalities (MRM vs. BCS) were analyzed using the Kaplan-Meier method and the log-rank test.  At a median follow-up of 72 months (range, 24-150 months), the 5-year overall survival (OS) rates in the BCS group were 98.2 % and 88.7% in the MRM group (P=0.012), and the corresponding 5-year disease-free survival (DFS)  Meier method, log-rank test were 98.2 and 82.1%, respectively (P=0.073). Libyan women with early-stage breast cancer: MRM was applied in 74.7% of patients, and only 25.3% of patients underwent BCS. Patients who underwent MRM were associated with poorer prognosis (P=0.012) and an increased rate of recurrence. At a median follow-up of 72 months (range, 24-150 months), the 5-year overall survival (OS) rates in the BCS group were 98.2 % and 88.7% in the MRM group (P=0.012), and the corresponding 5-year disease-free survival (DFS) rates were 98.2 and 82.1%, (P=0.073) respectively. Libyan women with early-stage breast cancer: MRM was applied in 74.7% of patients, and only 25.3% of patients underwent BCS. Patients who underwent MRM were associated with poorer prognosis (P=0.012) and an increased rate of recurrence.